2022
DOI: 10.1002/hsr2.576
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep disturbance in alopecia areata: A cross‐sectional study

Abstract: Background Alopecia areata (AA) is a nonscarring hair loss with autoimmune pathophysiology, which is associated with psychiatric disorders including anxiety and depression. Sleep disorders are commonly seen with anxiety and depression. Here we evaluate the sleep quality of AA patients. Methods This cross‐sectional study involved 51 AA patients and 51 age‐ and sex‐matched healthy controls. The sleep quality and day sleepiness were evaluated by the Pittsburgh Sleep Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…In this regard, there are few studies addressing the issue of sleep quality in patients suffering from AA. One study exploring sleep quality in AA [ 25 ] was in line with the results of the present report: patients with AA seem to have higher PSQI scores than controls, as well as higher rates of daytime sleepiness. Moreover, as the present study shows, anxiety and depression are also more frequent among patients with AA than among controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this regard, there are few studies addressing the issue of sleep quality in patients suffering from AA. One study exploring sleep quality in AA [ 25 ] was in line with the results of the present report: patients with AA seem to have higher PSQI scores than controls, as well as higher rates of daytime sleepiness. Moreover, as the present study shows, anxiety and depression are also more frequent among patients with AA than among controls.…”
Section: Discussionsupporting
confidence: 91%
“…In light of the results, sleep quality should be considered as an indicator of a poorer quality of life and mood status disturbances in patients with AA, as it correlates with poor quality of life, anxiety and depression scores independently of the severity of the disease. Similar studies [ 25 ] have found consistent results: sleep quality scores do not seem to correlate with the severity of the disease, whereas they do with anxiety and depression rates. It is possible that the remitting and recurrent course of AA results in a poorer sleep quality as well as in higher rates of anxiety and depression, related to the chronic condition itself, without being directly related to the severity of the disease at a specific point in time.…”
Section: Discussionsupporting
confidence: 76%
“…Four cross-sectional studies, three cohort studies, and one case-control research were evaluated for bias; the 8 cross-sectional, cohort, and case-control studies all showed a medium risk of bias. One major risk of bias in all cross-sectional studies which failed to report the number of non-respondents [ 20 , 21 , 23 , 24 ]. Shakoei et al did not employ a sizable patient population [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…One major risk of bias in all cross-sectional studies which failed to report the number of non-respondents [ 20 , 21 , 23 , 24 ]. Shakoei et al did not employ a sizable patient population [ 20 ]. The failure to report the number of individuals lost due to follow-up was one main bias observed in all cohort studies [ 1 , 15 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…AA is a skin disease, which has been previously linked to a poor quality of life in patients [ 22 , 23 ]. However, to date, no studies have assessed the burden that this disease has on the patient’s cohabitants.…”
Section: Discussionmentioning
confidence: 99%